Kinerja Keuangan LPD Dalam Perspektif Budaya Tri Hita Karana - Mertyani Sari Dewi; Putu Eka Nopiyani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
Abstract. The results of the study prove that the development of the ROA (Return On Asset) Ratio from 2017-2021 dominantly decreased, namely in 2017-2019 this was due to the fact that in 2019 the increase in profit was smaller than the increase in assets. The decline in 2020 and 2021 occurred due to the declining profit value but the number of assets owned by the LPD increased. The reversed condition is illustrated in 2018, namely the ROA value has increased from the previous year, this occurs because profits have increased but the number of assets has decreased. When viewed from the average ROA value from 2017-2021 only in 2020 and 2021 the ROA value of LPD Penglatan is below the average. Based on the development of profits obtained from 2017 – 2021 and CSR funds distributed, fluctuated in 2018 increasing by 9.92% and in 2019 increasing 9.57%. The reverse condition is illustrated in 2020 and 2021 which illustrates the value of profits and CSR funds that have decreased by 15.76% in 2020 and in 2021 it has decreased by 10.44%. However, the average profit increased 1.68%. Likewise, the CSR provided has fluctuations where the average increase is every year 2017-2021, fluctuations that follow the trend trend are the same as changes in profit.